2012
DOI: 10.1007/s00115-012-3485-x
|View full text |Cite
|
Sign up to set email alerts
|

Das Erleben der Aufnahme in eine psychiatrische Klinik

Abstract: Principally the QAE-P seems to be a suitable instrument of quality management. A number of factors were identified that show associations with the subjective evaluation of admission as reported by the patients. Some of these variables are within the control of the clinical management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
0
3
0
4
Order By: Relevance
“…In psychotic patients who were admitted for the first time, 80% described treatment as traumatic and 38% were diagnosed with posttraumatic stress disorder associated with admission [16]. A German study found that admission to an open ward was associated with a more positive experience than admission to a locked ward [17]. Furthermore, opening and locking doors may increase the workload for nurses and reduce time for engagement in therapeutic activities with patients [13,14,18].…”
Section: Introductionmentioning
confidence: 99%
“…In psychotic patients who were admitted for the first time, 80% described treatment as traumatic and 38% were diagnosed with posttraumatic stress disorder associated with admission [16]. A German study found that admission to an open ward was associated with a more positive experience than admission to a locked ward [17]. Furthermore, opening and locking doors may increase the workload for nurses and reduce time for engagement in therapeutic activities with patients [13,14,18].…”
Section: Introductionmentioning
confidence: 99%
“…The study used the FEA-P questionnaire (translated into Polish and then verified by back translation) consisting of 33 questions grouped in seven dimensions rated by patients (Table 2). The content of the items of this tool was diligently verified by its German authors, therefore it presents key aspects of the studied phenomenon [9]. The translation of the subscale names focused on the best possible wording and clinical meaning of the subscales in the setting of Polish psychiatric care.…”
Section: Toolsmentioning
confidence: 99%
“…Martin Driessen i wsp. [9] podjęli próbę operacjonalizacji opinii pacjentów w momencie hospitalizacji poprzez FEA-P, tj. Kwestionariusz subiektywnego przeżywania sytuacji przyjęcia do szpitala psychiatrycznego (niem.…”
Section: Toolsunclassified
See 2 more Smart Citations